Analisis Perbandingan Kinerja Keuangan pada PT Bank Central Asia Tbk Sebelum dan Sesudah Akuisisi PT Bank Interim Indonesia (PT Bank Rabobank International Indonesia) - Mafiana , Della; Murwanti, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to investigate whether there are differences in financial performance before and after the acquisition of PT Bank Central Asia Tbk by PT Bank Interim Indonesia (PT Bank Rabobank International Indonesia). The financial ratios used are CAR, ROA, ROE, NIM, BOPO, and LDR. This is a quantitative research with a comparative research design. The data used are secondary data from the quarterly financial reports of PT Bank Central Asia Tbk for a period of 5 years (2018-2022). The data analysis method used is the paired sample t-test and wilcoxon test with the help of SPSS software. The results of the paired sample t-test show that the CAR and LDR variables show significant differences, while the ROA and ROE variables do not show significant differences between the period before and after the acquisition. The wilcoxon test for NIM and BOPO variables shows that the NIM variable shows significant differences, while the BOPO variable does not show significant differences between the period before and after the acquisition.